2016
DOI: 10.1016/j.neuroscience.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic function during sleep-like brain states in urethane anesthetized rats

Abstract: HighlightsSpontaneous changes in sleep-like EEG state occur in urethane-anesthetized rats.The micturition threshold is increased during the slow wave sleep-like state.Micturition-related activity of PAG neurons was reduced during slow wave EEG states.Changes in sleep-like EEG state may impact PAG-mediated control of bodily systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…; Pagliardini et al . , , b ; Crook & Lovick, ; Walczak & Blasiak, ). During our recordings, we observed spontaneous brain state alternations expressed as cyclic changes in the ECoG.…”
Section: Resultsmentioning
confidence: 99%
“…; Pagliardini et al . , , b ; Crook & Lovick, ; Walczak & Blasiak, ). During our recordings, we observed spontaneous brain state alternations expressed as cyclic changes in the ECoG.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that in urethane anaesthetized animals cyclic alternations of brain state and accompanying changes in physiological parameters and neuronal activity are observed (Clement et al ., ; Brown et al ., ; Whitten et al ., ; Devonshire et al ., ; Pagliardini et al ., , ,b; Sakata & Harris, ; Petzold et al ., ; Crook & Lovick, ). Urethane anaesthetized animals are widely used to study neurophysiology of dopaminergic system.…”
Section: Introductionmentioning
confidence: 99%
“…The role of PAG in control of the bladder function encompasses both spinal and cortical connections. The PAG has functionally [34] and histologically [35] separate columns. These columns can be divided into two functionally separate groups having opposite autonomic functions, the ventrolateral column having parasympathetic function and the lateral and dorsolateral columns which have sympathetic functions [36,37].…”
Section: Periaqueductal Gray Matter the Headquarter Of Bladder Controlmentioning
confidence: 99%
“…Chemical stimulation of the vlPAG by D,L-homocysteic acid (DLH) in rats increases the frequency of micturition [34]. On the other hand, stereotaxic injection of the inhibitory mediator cobalt chloride into the caudal vlPAG reversibly attenuates bladder contractions and external urethral sphincter (EUS) electromyographic activity in rats [35]. Injection of other inhibitory or stimulatory agents, CoCl2 and L-glutamate, into the vlPAG lead to suppression or stimulation of voiding in rats, respectively [36].…”
Section: The Vlpag As the Major Pag Column With Connections To The Blmentioning
confidence: 99%
See 1 more Smart Citation